Pengaruh Perbedaan Metode Produksi Terhadap Karakteristik Fisikokimia dan Organoleptik Gula Semut Aren: Effect of Different Production Methods on Physicochemical and Organoleptic Characteristics of Palm Granulated Sugar - Meikapasa, Ni Wayan Putu; Ulpiana, Mia; Putri, Nadila (Universitas Bumigora, 2025)
Granulated palm sugar is a natural sweetener product that is gaining popularity due to its low glycemic index and its beneficial health effects. There are two primary methods of producing palm sugar: direct production from fresh sap and reprocessing of molded palm sugar. This study aims to investigate the impact of various production methods on the physicochemical and organoleptic properties of granulated palm sugar. The research employed a Completely Randomized Design (CRD) with one factor, namely the cooking method, consisting of direct production from fresh sap (PL) and production through reprocessing molded sugar (PC). The observed parametersincluded moisture content, ash content, yield, reducing sugar content, and organoleptic tests covering color, aroma, taste, and texture. The analysis results showed significant differences in all tested physicochemical parameters. The PC granulated palm sugar had a lower moisture content, yield, reducing sugar content compared to PL and higher ash content. In the organoleptic tests, PC palm sugar scored significantly higher in terms of color, aroma, taste, and texture. This study concludes that the production method using molded sugar is more recommended, as it produces palm sugar with a more stable quality, meets the standard, and is more preferred by consumers. This research is expected to serve as a basis for determining the appropriate method for producing high-quality granulated palm sugar.